Academic programme internationalisation: the setting up of guidelines for international students admission requirements to Universiti Utara Malaysia - Abdul Karim, Abdul Malek; Mustaffa, Che Su; Saidin, Khaliza; Ku Ishak, Awanis; Mohammed Nazir, Mohamed Azri; Mohammed Isa, Abdul Rahman (2016)
This study aims to find out the various academic systems adopted by other countries and to develop standardized admission requirements for international students aspiring to further their studies at Universiti Utara Malaysia (UUM).To gather its data, this study used three data collection methods which are document analysis, face-to-face interview and focus group interview among international students studying in UUM and Embassy officials of countries which have students studying in UUM. The study found that most universities adopt three systems: British, French and the US system. In terms of grading system, it was found that three assessment systems were used, namely average grade point, percentage and cumulative grade point average.These three grading systems were key factors in the setting up of standardized admission requirements for international students to UUM to ensure each application receives proper consideration by the university. It was also hoped that the grading system created based on this study would make it possible for international applicants to make an online check whether they meet the requirement of the university before submitting their applications.